PERSEPSI GURU TERHADAP PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) SEBAGAI MEDIA PEMBELAJARAN EDUKATIF DI SEKOLAH DASAR - Putri Wulandari; Eka Sastrawati; Issaura Sherly Pamela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore teachers’ perceptions of utilizing Artificial Intelligence (AI) as an educational learning medium in elementary schools. Conducted at SDN 42/IV Kota Jambi, this qualitative case study employed observations, interviews, and documentation to collect data from teachers who actively use AI in planning and implementing learning. The findings indicate that teachers perceive AI as a functional digital tool that assists in preparing materials, creating visual media, and enhancing the variety and interactivity of learning. Teachers demonstrate positive and adaptive attitudes, using AI selectively according to students’ needs while maintaining pedagogical oversight. The effectiveness of AI integration is influenced by school support, including infrastructure, leadership, and collaborative culture, as well as strategies to overcome technical and pedagogical challenges. Overall, teachers effectively utilize AI, although further development in training and institutional support is recommended to maximize its pedagogical potential.